2006
DOI: 10.1007/s10620-006-9337-4
|View full text |Cite
|
Sign up to set email alerts
|

Celiac Disease Prevalence in Brazilian Dilated Cardiomyopathy Patients

Abstract: Celiac disease (CD) is a permanent condition of gluten intolerance and a number of autoimmune diseases have been associated with it. In the past few years, a relation between CD and dilated cardiomyopathy (CM) was described in Europe and United States. The aim of this study was to evaluate the prevalence of CD among south Brazilian precardiac transplant patients with advanced CM. A total of 74 patients on a list for heart transplantation were evaluated for the presence CD. The presence of anti-endomisial antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 29 publications
0
22
0
1
Order By: Relevance
“…However, the number of patients has been relatively small, ranging from 1 to 4 patients with both CD and DCM diagnoses in each study. 12,14,15 The present study identified 17 patients with CD and patient chart–validated idiopathic DCM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the number of patients has been relatively small, ranging from 1 to 4 patients with both CD and DCM diagnoses in each study. 12,14,15 The present study identified 17 patients with CD and patient chart–validated idiopathic DCM.…”
Section: Discussionmentioning
confidence: 99%
“…Most research on CD and DCM 1214 has examined the prevalence of CD in patients with DCM. To our knowledge, only 2 studies have examined the risk of DCM in CD, 15,16 but these studies were restricted to information on CD and DCM from inpatient registers.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported an increased prevalence of CD in patients with dilated cardiomyopathy (DCM). [78] Frustaci et al . [9] have reported a relatively high CD prevalence in a large cohort of patients with biopsy-proven myocarditis.…”
mentioning
confidence: 99%
“…However, there have been few attempts to systematically study such a link. Some studies have searched for coeliac disease in cohorts of patients with dilated cardiomyopathy and reported the prevalence of coeliac to be higher than would be expected in the general population 14 15. However, other studies of dilated cardiomyopathy patients have not found any increased prevalence of coeliac disease 16…”
Section: Discussionmentioning
confidence: 99%